Essential Oils from Ugandan Medicinal Plants: In Vitro Cytotoxicity and Effects on IL-1𝛽-Induced Proinflammatory Mediators by Human Gingival Fibroblasts - Ocheng, Francis; Bwanga, Freddie; Boström, Elisabeth Almer; Joloba, Moses; Karlson, Anna-Karin Borg; Lindberg, Tülay Yucel; Obua, Celestino; Gustafsson, Anders (Evidence-Based Complementary and Alternative Medicine, 2016)
The study investigated cytotoxicity of essential oils from four medicinal plants (Bidens pilosa, Ocimum gratissimum, Cymbopogon nardus, and Zanthoxylum chalybeum) on human gingival fibroblasts and their effects on proinflammatory mediators’ secretion. Cytotoxicity of essential oils was investigated using 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide assay. Effects of essential oils at subcytotoxicity concentrations on interleukin- (IL-) 6, IL-8, and prostaglandin E2 (PGE2) secretions by gingival fibroblasts treated with IL-1𝛽 (300 pg/mL) were evaluated by ELISA and EIA. IC50 values of the essential oils ranged from 26 𝜇g/mL to 50 𝜇g/mL. Baseline and IL-1𝛽-induced secretion of PGE2 was inhibited by treatment with essential oil from O. gratissimum. Essential oils from B. pilosa and C. nardus had synergistic effects with IL-1𝛽 on PGE2 seceretion. In conclusion, the study suggests that essential oil from O. gratissimum decreases gingival fibroblasts secretion of PGE2, while essential oils from B. pilosa and C. nardus increase PGE2 secretion. Essential oil from Z. chalybeum was the most cytotoxic, while oil from C. nardus was the least cytotoxic. Although the clinical significance of these findings remains to be determined, it may be suggested that essential oil from O. gratissimum, applied at subcytotoxicity concentrations, could reduce the participation of gingival fibroblasts in the gingival inflammation and tissue destruction associated with periodontitis
Keywords: Medicinal Plants; Mediators; Human; Essential oils